Knowing Nature Through History. Issue 12 (December 2013) - Piper, Liza
Abstract This essay surveys the past 20 years of Canadian environmental historiography in order to understand how scholars in this field have conceptualized and applied nature to the study of the past. The essay argues that Canadian environmental historians, even as they foreground nature as an historical actor, nevertheless continue to focus their attention and orient their investigations around questions of how human social, cultural, economic, and political power reshaped both nature and human experience in the past. This emphasis is not interpreted as fundamentally problematic. However, the author maintains that it is important for environmental historians to recognize that their practices diverge from their prescriptions in this regard and that practitioners should continue to push toward new ways of incorporating nature into Canadian historiography.